La deuda y el apalancamiento:¿ aliado estratégico o enemigo empresarial? - Quimi Espinoza, Katherine Daniela; Zeas Asanza, Jonathan Stalin (My University, 2021)
Debt and corporate leverage have a direct impact on the capital structure and therefore on its profitability, which is the basis that the objective of this research lies in an exhaustive analysis of the different nuances implicit in the use of debt and leverage in organizations, for which a qualitative approach was applied with a descriptive scope based on a bibliographic type modality since the information obtained is of a documentary type and is related to the variables of debt and leverage that is complemented by the practical exemplification of conceptualizations collected from academic sources, scientific articles, books, official websites, business newsletters, and reports. With this it is concluded that a financial analysis based on timely tools such as financial ratios and the consideration of various exogenous and endogenous factors related to open companies found the probability of reaching an optimal capital structure from the business point of view. Similarly, the inadequate management of the tools designed for decision-making can become a barrier that prevents the growth of organizations.
La deuda y el apalancamiento empresarial tienen una incidencia directa en la estructura de capital y por ende en la rentabilidad, lo cual fundamenta que el objetivo de la presente investigación radica en un análisis exhaustivo de los diferentes matices que trae implícito el uso de la deuda y el apalancamiento en las organizaciones, para lo cual se aplicó un enfoque cualitativo con un alcance descriptivo basado en una modalidad de tipo bibliográfica ya que, la información obtenida es de tipo documental y se encuentra relacionada a las variables de deuda y apalancamiento que se complementa con la ejemplificación práctica de las conceptualizaciones recopiladas de fuentes académicas, artículos científicos, libros, sitios web oficiales, boletines empresariales e informes. Con esto se concluye que, un análisis financiero basado en herramientas oportunas como son los ratios financieros y la consideración de diversos factores exógenos y endógenos conexos a las empresas aumentan la probabilidad de alcanzar una estructura de capital óptima desde el punto de vista empresarial. De igual manera la inadecuada gestión de las herramientas diseñadas para la toma de decisiones puede constituirse en una barrera que impida el crecimiento de las organizaciones.
Keywords: ESTRUCTURA DE CAPITAL; APALANCAMIENTO